0691 A Comparison Of The Discrepancy Between Self-reported And Objectively Measured Sleep At Home And In The Laboratory. (12th April 2019) - Khou, Christina S; Hamilton, Nancy; Siengsukon, Catherine; Watts, Amber
Abstract: Introduction: Older adults are a growing segment of the population who experience disturbed sleep. Researchers have found that there is a discrepancy between actigraphy and self-report in older adults with co-morbid medical conditions and that this discrepancy is affected by individual characteristics. However, this relationship and discrepancy is unclear in healthy older adults. The purpose of this study was to determine the difference between actigraphy and diary estimates of sleep onset latency (SOL) and total sleep time (TST), and to determine how sleep quality, depressive symptoms, and memory are associated with the difference between actigraphy and sleep diary estimates of sleep. Methods: Data were gathered from 78 participants ( M age = 74.06 years-old, SD= 6.65). A majority were female (69%) and White/Caucasian (96%). Participants completed sleep diaries (i.e., subjective sleep), questionnaires (Geriatric Depression Scale, Pittsburgh Sleep Quality Index, immediate and delayed recall tasks), and wore actigraphs (i.e., objective sleep) for 4-7 nights ( M nights = 6.88, SD= 0.46). Differences between total sleep time (TST) and sleep onset latency (SOL) were calculated by subtracting sleep diary self-reports from actigraphy sleep estimates. Results: Multiple Wilcoxin Signed-Rank tests were conducted to examine the discrepancy between self-reported and actigraphy measured SOL and TST. Self-reported SOL was significantly greater than actigraphy measured SOL (z= 6.95, p <.001). Self-reported TST was greater than actigraphy measured TST (z= 2.51, p= .014). Multilevel regression models revealed that participants who reported worse sleep quality had a greater discrepancy between their sleep diary and actigraphy estimated SOL (γ= 1.69, SE = 0.42, p < .01). Conclusion: Results demonstrated that healthy older adults perceived taking longer to fall asleep and sleeping more than what was indicated from actigraphy data. Worse sleep quality predicted a greater incongruence between self-reported and actigraphy estimated sleep onset latency. Future studies should continue to investigate how psychological and physiological functioning and processes impacts the discrepancy between self-reported and actigraphy estimated sleep in healthy older adults and explore the longitudinal pattern of this discrepancy. Support (If Any)